Organizational Health: A Study Of A Malaysian Private Higher Learning Institution - Hong, Kian Sam; Lily, Law; Agnes Mary, Toner (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study examined the organizational health of a private institution of higher learning in Malaysia. The relationships between the seven dimensions of organizational health and five demographic variables were also investigated. The seven dimensions of organizational health, based on the Organizational Health Inventory (OHI), were academic emphasis, consideration, initiating structure, institutional integrity, resource support, morale, and upper management influence. The five demographic variables studied were age, education level, gender, length of service and marital status. The research design for this study was a cross sectional sample of the population using a questionnaire as the study instrument. The participants were 120 full time staff of the institution and 78 usable questionnaires were returned. The findings indicated that overall the private institution of higher learning was moderately healthy, and the order of occurrences of the seven dimensions of organizational health was: initiating structure and institutional integrity (slightly above average), and morale, upper management influence, resource support, academic emphasis and consideration (moderate). There were no significant differences in the perceptions of organizational health based on gender, age, length of service and marital status. The findings of this research indicated that the organizational health of the private institution of higher learning being studied could be improved through enhancing its staff morale, having more interactions between staff with different levels of responsibilities, providing more resources for its core business of teaching and learning, management showing considerations to its staff, and emphasizing academic excellence.